Financial Innovation and the Role of Derivative Securities: An Empirical Analysis of the Treasury STRIPS Program - Grinblatt, Mark; Longstaff, Francis A. (Journal of Finance, 2000)
The role that financial innovation plays in financial markets is very controversial. To provide insight into this role, we examine how market participants use the highly successful Treasury STRIPS program. We find that investors use the option to create Treasury‐derivative STRIPS primarily to make markets more complete and take advantage of tax and accounting asymmetries. Although liquidity‐related factors help explain differences in the prices of Treasury bonds and STRIPS, we find little evidence that the option to strip and reconstitute securities is used for speculative or arbitrage‐related purposes.